2019
DOI: 10.7899/jce-18-11
|View full text |Cite
|
Sign up to set email alerts
|

Predicting stress and test anxiety among 1st-year chiropractic students

Abstract: Objective: We evaluated perceived stress in 1st-year chiropractic students and the relationship between perceived stress and test anxiety. Moreover, we sought student-identified stressors that complicate chiropractic education. Methods: We tested 3 hypotheses in a longitudinal descriptive study: (1) student-perceived stress would increase over 6 months of chiropractic training, (2) depression level and grade-point average (GPA) at matriculation would predict student-perceived stress 6 months into the program, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 54 publications
3
0
0
Order By: Relevance
“…These results we obtained are consistent with the nature of Generalized anxiety disorder (GAD) as individuals diagnosed with GAD have low self-esteem, worry excessively about everyday life, and feel like they cannot control their worry so it is a possibility that this anxiety or worry about the academics is surfacing as being unsatisfied with the academic performance. A similar result to ours was found in a longitudinal study about perceived stress among chiropractic students in Iowa in which pre-matriculation GPA was not a predictor of perceived stress [ 52 ]. In contrast, a study in Malaysia established a weak and negative relationship between stress and academic achievement [ 53 ].…”
Section: Discussionsupporting
confidence: 88%
“…These results we obtained are consistent with the nature of Generalized anxiety disorder (GAD) as individuals diagnosed with GAD have low self-esteem, worry excessively about everyday life, and feel like they cannot control their worry so it is a possibility that this anxiety or worry about the academics is surfacing as being unsatisfied with the academic performance. A similar result to ours was found in a longitudinal study about perceived stress among chiropractic students in Iowa in which pre-matriculation GPA was not a predictor of perceived stress [ 52 ]. In contrast, a study in Malaysia established a weak and negative relationship between stress and academic achievement [ 53 ].…”
Section: Discussionsupporting
confidence: 88%
“…These results we obtained are consistent with the nature of Generalized anxiety disorder (GAD) as individuals diagnosed with GAD have low self-esteem, worry excessively about everyday life, and feel like they cannot control their worry so it is a possibility that this anxiety or worry about the academics is surfacing as being unsatis ed with the academic performance. A similar result to ours was found in a longitudinal study about perceived stress among chiropractic students in Iowa in which pre-matriculation GPA was not a predictor of perceived stress [52]. In contrast, a study in Malaysia established a weak and negative relationship between stress and academic achievement [53].…”
Section: Discussionsupporting
confidence: 87%
“…This study also confirmed that students with lower income obtain higher PSS scores, which is consistent with the findings of other authors such as Cohen and Janicki-Deverts [55] or Klein and colleagues [56]. Accordingly, it is possible to agree with the authors Zhang and Henderson [112], who argued that finance is a significant stress factor. Regarding the PHQ 9 score, the differences were not as obvious as in the previous case and a significant difference (at the level of 0.01) was found only in the income characteristics, while higher PHQ 9 score was observed in lower-income students.…”
Section: Prevalence and Levels Of Stress Depression And Alcohol Use supporting
confidence: 92%